Experimental investigation of free vibration analysis on fibre metal composite laminates - M. N. M., Merzuki; M. R. M., Rejab; M. S. M., Sani; Zhang, Bo; Quanjin, Ma (UMP Press, 2019)
Fibre-metal laminates (FMLs) offer advanced improvements over current available structural materials due to the excellent mechanical properties. In this work, the dynamic behaviour of the carbon fibre/epoxy, glass fibre/epoxy, aluminium 2024-T0, and fibre metal laminates were carried out. Furthermore, the different type of reinforced composites in FMLs and the effect of the layer sequence of metal layers were investigated. The composite laminates have been manufactured by a hot press machine. The free vibration tests were conducted to determine the dynamic characteristics of the samples. The accuracy of the experimental results was verified by comparing the numerical analysis results. The results indicate that the effect of thickness and the layer sequences of metal layers have a significant effect on the natural frequency of the FMLs.